Moni the goat boy - Spyri, Johanna, 1827-1901.; Copeland, Charles, 1858-1929 (New York : T.Y. Crowell, 1914)
After he reluctantly agrees to keep another boy's secret in exchange for the life of one of the goats he tends, Moni loses his cheerful disposition and love of singing until he finally decides to reveal the truth.
Mode of access: Internet.
Keywords: Switzerland -- Fiction; Alps -- Fiction